AKTIVITAS SHARENTING DAN PRAKTIK KOMODIFIKASI ANAK (Studu Netnografi pada Akun TikTok @ndhiraa07) - Nirmala Hastutik, Renta; Bayu Widagdo, Muhammad; Lukmantoro, Triyono (Interaksi Online, 2024)
The phenomenon of sharenting, where parents share their children's activities on social media, has emerged from the evolving parenting patterns in the digital world. Initially, it was about sharing everyday moments, but now children gain popularity that parents exploit for personal gain. This activity threatens children's privacy and rights, as their personal information is widely disseminated without their consent. Content commodification occurs, turning the child's private life into a tool for profit. This study employs Social Network Theory, Communication Privacy Management Theory, and Political Economy of Media Theory using netnography on the TikTok account @ndhiraa07. The findings indicate that sharenting activities include the child's daily routines, packaged entertainingly while also being educational, motivational, and shaping the image of a good young mother. Although sharing everyday activities, content commodification is evident where the child's popularity is leveraged for profit through content exposure and endorsement practices, resulting in high engagement in the form of views, likes, and comments. The child's privacy is violated by blurring private and public spaces.